ナンキョク ケンキュウ カガク イインカイ ノ レンゾク プランクトン サイシュウキ センモンカ グループ ワークショップ ホウコク - 高橋, 邦夫; タカハシ, クニオ; Hosie, Graham W.; Kitchener, John A.; McLeod, David J.; Stevens, Catherine; Robinson, Karen; Jonas, Tanya; 福地, 光男; フクチ, ミツオ; Takahashi, Kunio T.; McLeod , David J.; et al. (2011)
P(論文) 2010年11月22-26日に国立極地研究所にて「南極研究科学委員会(以下SCAR)連続プランクトン採集器(以下CPR)専門家グループワークショップ」を開催した.4カ国から12名が参加し,南大洋CPR観測実務担当者の間で,観測データの品質管理,種同定やデータ分析手法の再確認,及び今後の活動についての詳細な討議を行った.前半は文献資料及び顕微鏡観察を通して,動物プランクトンの分類群ごとに種同定の情報交換及び具体的な分類カテゴリーの統一を図った.まとめられた種同定基準を用いて新たにマニュアルを作成することとなった.後半はデータ分析手法とデータマネージメント,さらには将来的な観測計画を確認した.今後,定期的にワークショップを開催し,各国間で統一された試料処理及びデータ管理を維持していくことで合意した. "Southern Ocean Continuous Plankton Recorder (SO-CPR) Standards Workshop: SCAR Expert Group on CPR Research" was held at the National Institute of Polar Research (NIPR) on 22-26 November 2011. Twelve participants from four countries attended. The purposes of the workshop were to ensure that consistent and high standards of species identification, methodology, and data quality were being maintained amongst all participants and laboratories in the SO-CPR survey, and to discuss future contributions of the SO-CPR program to a global CPR network. The first three and a half days of the workshop were focused on assessing the accuracy and consistency of species identifications. We concluded that our species identifications and procedures are accurate and uniform, and that the SO-CPR database is of the highest possible standard. Certain taxonomic criteria developed at the workshop will be described in a new laboratory procedures manual. Four major gaps in the database (spatial, temporal, taxonomic, and data analysis gaps) were identified and discussed. Participants concurred that there should be more regular workshops to ensure that the high standards of the SO-CPR program are maintained. Errata | http://id.nii.ac.jp/1291/00009645/ departmental bulletin paper